The pleiotropic functions of Pri smORF peptides synchronize leg development regulators - Markus, Damien; Pelletier, Aurore; Boube, Muriel; Port, Fillip; Boutros, Michael; Payre, François; Obermayer, Benedikt; Zanet, Jennifer (PLoS Genetics, 2023)
The last decade witnesses the emergence of the abundant family of smORF peptides, encoded by small ORF (<100 codons), whose biological functions remain largely unexplored. Bioinformatic analyses here identify hundreds of putative smORF peptides expressed in Drosophila imaginal leg discs. Thanks to a functional screen in leg, we found smORF peptides involved in morphogenesis, including the pioneer smORF peptides Pri. Since we identified its target Ubr3 in the epidermis and pri was known to control leg development through poorly understood mechanisms, we investigated the role of Ubr3 in mediating pri function in leg. We found that pri plays several roles during leg development both in patterning and in cell survival. During larval stage, pri activates independently of Ubr3 tarsal transcriptional programs and Notch and EGFR signaling pathways, whereas at larval pupal transition, Pri peptides cooperate with Ubr3 to insure cell survival and leg morphogenesis. Our results highlight Ubr3 dependent and independent functions of Pri peptides and their pleiotropy. Moreover, we reveal that the smORF peptide family is a reservoir of overlooked developmental regulators, displaying distinct molecular functions and orchestrating leg development.
Gesehen am 05.06.2024